A new ornithophilous yellow-flowered Vriesea (Bromeliaceae) from Serra do Caraça, Minas Gerais, Brazil - Versieux, Leonardo M.; Machado, Talita Mota (Phytotaxa, 2012)
Vriesea marceloi is described as a new species and is illustrated. It is compared with V. claudiana, V. clausseniana and V. stricta, which we assume are the morphologically most similar species. The new species is related to the “V. minarum complex”, which groups yellow-flowered rupicolous taxa occurring on isolated mountain tops in southeastern Brazil, as well as to V. clausseniana, which shares the habitat with the new taxon. Pictures of the plants in the habitat, photos of the holotype, and a morphological comparative table are provided.